Dynamic splitting behaviour of ultra-high-performance concrete confined with carbon-fibre-reinforced polymer. (15th March 2022) - Huang, Liang; Su, Linwang; Xie, Jianhe; Lu, Zhongyu; Li, Pingjie; Hu, Ruolin; Yang, Shuai
Abstract: Fibre-reinforced polymer (FRP) wrapping is highly effective in enhancing the compressive properties of concrete. However, the dynamic splitting performance of FRP-confined ultra-high-performance concrete (UHPC) remains unexplored. This study investigated the impact resistance of carbon FRP (CFRP)-confined UHPC under splitting loads. The UHPC cylinders were wrapped in CFRP jackets of thicknesses from one to three plies. Several impact tests were conducted using a Ø100mm split Hopkinson pressure bar apparatus at different strain rates ranging from 2 s −1 to 17 s −1 . The dynamic behaviours of the specimens were investigated and compared with those under quasi-static loading. The results indicated that the splitting properties of UHPC exhibited a strong strain-rate dependency; however, the confinement of CFRP reduced the strain-rate sensitivity of UHPC. The rupture of the CFRP following UHPC cracking governed the failure of CFRP-confined UHPC under dynamic splitting loads. Although the quasi-static splitting tensile strength could be improved approximately linearly by the CFRP confinement ratio, the CFRP confinement effect decreased with increasing strain rate. A new model that considers the effects of confinement ratio and core concrete inertia is proposed to predict the splitting tensile strength of CFRP-confined UHPC under impact loading.